Pengaruh Kualitas Produk, Kualitas Pelayanan dan Harga terhadap Keputusan Pembelian pada Caffe Roemah Kreo di Lampung - Muhammad Fahmi Saputro; Is Fadhillah; Anis Fitriyasari (CV Edujavare Publishing, 2024)
This study aims to analyze the influence of product quality, service quality, and price on purchasing decisions at Caffe Roemah Kreo in Lampung. Product quality, service quality, and price are important factors that can influence consumer purchasing decisions in the competitive café industry. This research uses a quantitative method with a survey technique. Data were collected through questionnaires distributed to 150 respondents who are customers of Caffe Roemah Kreo. Data analysis was performed using multiple linear regression to determine the effect of each independent variable on the dependent variable. The results of the study show that the three variables, namely product quality, service quality, and price, significantly influence purchasing decisions. Product quality has the most dominant influence with the largest regression coefficient, followed by service quality and price. These findings indicate that customers prioritize product quality in making purchasing decisions, but service quality and price also play important roles. Based on these findings, the management of Caffe Roemah Kreo is advised to continuously improve product quality by maintaining consistency and the quality of raw materials. Additionally, improving service quality through employee training and facility enhancements is also necessary. Setting competitive prices that match the perceived value received by customers is another crucial factor for attracting and retaining customers. This study has limitations in terms of the sample size and location, which is restricted to one café. Future research is recommended to expand the scope by involving more cafés and a larger sample size, as well as using different research methods to gain deeper insights.